Evolutionary history of asexual hybrid loaches (Cobitis: Teleostei) inferred from phylogenetic analysis of mitochondrial DNA variation - Janko, K; Kotlík, P; Ráb, P (Journal of evolutionary biology, 2003)
Reconstruction of the evolutionary history of asexual lineages undermines their suitability as models for the studies of evolutionary consequences of sexual reproduction. Using molecular tools we addressed the origin, age and maternal ancestry of diploid and triploid asexual lineages arisen through the hybridization between spiny loaches Cobitis elongatoides, C. taenia and C. tanaitica. Reconstructions of the phylogenetic relationships among mitochondrial DNA (mtDNA) haplotypes, revealed by sequence analyses, suggest that both hybrid complexes (C. elongatoides-taenia and C. elongatoides-tanaitica) contained several asexual lineages of independent origin. Cobitis elongatoides was the exclusive maternal ancestor of all the C. elongatoides-tanaitica hybrids, whereas within the C. elongatoides-taenia complex, hybridization was reciprocal. In both complexes the low haplotype divergences were consistent with a recent origin of asexual lineages. Combined mtDNA and allozyme data suggest that the triploids arose through the incorporation of a haploid sperm genome into unreduced ova produced by diploid hybrids.
Keywords: hybridizace genetická; Hybridization, Genetic; Animals; Cypriniformes; Phylogeny; Ploidies; Female; zvířata; biologická evoluce; nepohlavní rozmnožování; Biological Evolution; fylogeneze; máloostní; ploidie; Reproduction, Asexual; DNA, Mitochondrial; mitochondriální DNA; ženské pohlaví